2021
DOI: 10.3390/ijms22168667
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Transcriptional Expression Analysis of Annexin Genes in Capsicum annuum and Characterization of CaAnn9 in Salt Tolerance

Abstract: Annexin (Ann) is a polygenic, evolutionarily conserved, calcium-dependent and phospholipid-binding protein family, which plays key roles in plant growth, development, and stress response. However, a comprehensive understanding of CaAnn genes of pepper (Capsicum annuum) at the genome-wide level is limited. Based on the available pepper genomic information, we identified 15 members of the CaAnn gene family. Phylogenetic analysis showed that CaAnn proteins could be categorized into four different orthologous grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In addition, exon/intron compositions and distributions of the LiANNs had a strong correlation with phylogenetic tree, and the LiANNs clustered into the same branch shared the similar gene structure (Fig. 4 ), which was consistent with previous studies [ 39 ]. Totals of 0, 0, 3, 9, 9, and 11 orthologous ANN gene pairs were found through collinearity analysis of crape myrtle versus rice, grape, Arabidopsis, eucalyptus, poplar, and willow (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, exon/intron compositions and distributions of the LiANNs had a strong correlation with phylogenetic tree, and the LiANNs clustered into the same branch shared the similar gene structure (Fig. 4 ), which was consistent with previous studies [ 39 ]. Totals of 0, 0, 3, 9, 9, and 11 orthologous ANN gene pairs were found through collinearity analysis of crape myrtle versus rice, grape, Arabidopsis, eucalyptus, poplar, and willow (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, a genome-wide identification with strict standards revealed 9 ANN genes from L. indica and named LiANN1-9 based on the chromosome localization. Previous studies showed that the plant ANN family members were small, and the complexity as well as diversity of ANNs was low [ 39 ]. Here, a total of 39 ANN members were divided into 3 subfamilies (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant annexins, comprising a multigene family of calcium-dependent phospholipidbinding proteins, play a vital role in responding to environmental stresses and signaling pathways during the growth and development of plants. The role of annexin genes in plant abiotic stress has been extensively studied in various crops, such as Arabidopsis [37], durum wheat [38], pepper [39], cotton [40], maize [41], and rice [42]. Annexins have been shown to regulate the flow of Ca 2+ in the root epidermis, enhancing tolerance to salt, alkali, and osmotic stress.…”
Section: Discussionmentioning
confidence: 99%